Substantive representation of women in Asian parliaments - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2022)
Combining data from nearly 100 interviews with national parliamentarians from ten Asian countries, the contributors to this book analyze and evaluate the advancement of gender equality in Asia. As of the year 2022, no country in Asia has gender parity in its parliament. Meanwhile, the proportion of national-level women parliamentarians in Asia averages a mere 20%. What is more important than simple descriptive representation, however, is whether outcomes for women are improving. Rather than focusing on numerical representation, the chapters in this book focus on the substantive representation of women. In other words, what do women and men parliamentarians do to advance women’s well-being and gender equality? Using semi-structured interviews, the author of each chapter examines these efforts in the context of a specific Asian country. The case studies include Bangladesh, Indonesia, Japan, Malaysia, Nepal, the Philippines, South Korea, Sri Lanka, Taiwan, and Timor-Leste.The book is an essential resource for scholars and students of Asian politics and the politics of gender.